Attitude of Librarians toward Use of Social Networking Sites for Library Services Delivery in Selected Federal Universities in Nigeria - BICHI, IBRAHIM AHMED (MiddleBelt Journal of Library and Information Science, 2020)
This study examined the attitude of librarians toward the use of socialnetworking sites SNSs) for library services as well as the relationships between librarians’ demographic variables and their attitude toward the use of SNSs. The motivation for the study was anchored on the fact that previous studies had neglected research on the influence of librarians’ demographic variables and attitude towards adoption and use of SNSs. Twelve university libraries were selected based on their year of establishment and Nigeria’s geopolitical zones. Questionnaire was the instrument used for data collection from all the academic librarians of these universities. The instrument was validated by experts, and was found to be reliable at Crombach Alpha value of between 0.75 and 0.9 after running a reliability test. This study therefore, was an attempt to fill the gap that exists. The findings show that academic librarians have positive attitude toward use of SNS for library services. It further revealed that there were no statistical relationships between attitude toward SNSs and respondents’ gender while significant relationship exists between attitude toward SNSs and librarians’ age and educational qualifications. The research concludes that academic librarians had positive attitude toward use of SNSs for library services. Adoption and use of SNSs for library services by university libraries would prosper over time. It is recommended that libraries should further engage younger and more educated staff on the provision of services through SNSs.